2021
DOI: 10.1038/s41598-020-80888-9
|View full text |Cite
|
Sign up to set email alerts
|

Multistage heat treatment and the development of a protective oxide-scale layer on the surface of FeCrAl sintered-metal-fibers

Abstract: This study investigates the effects of Multistage Heat Treatment (MSHT) on the development of an oxide-scale layer on the surface of FeCrAl sintered-metal-fibers. The oxide-scale layer was developed using an MSHT cycle at 930 °C for 1 h, followed by 960 °C for 1 h, and finally at 990 °C for 2 h. In this study, three samples were considered: Sample 1 was kept without thermal oxidation, while Samples 2 and 3 were exposed to one and eighteen MSHT cycles. Thermo-gravimetric analyses show that the weight gain of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…Sample 2 was subjected to one MSHT cycle, while Sample 3 was subjected to multiple MSHT cycles. The results of Ibrahim et al [ 36 ] for one MSHT cycle were similar and confirmed the results presented by Samad et al [ 17 ]. However, after multiple MSHT thermal oxidation cycles, the oxide-scale layer evolved into a different microstructure and revealed diffraction pattern peaks of a stable α-Al 2 O 3 and crystalline Cr.…”
Section: Introductionsupporting
confidence: 89%
See 4 more Smart Citations
“…Sample 2 was subjected to one MSHT cycle, while Sample 3 was subjected to multiple MSHT cycles. The results of Ibrahim et al [ 36 ] for one MSHT cycle were similar and confirmed the results presented by Samad et al [ 17 ]. However, after multiple MSHT thermal oxidation cycles, the oxide-scale layer evolved into a different microstructure and revealed diffraction pattern peaks of a stable α-Al 2 O 3 and crystalline Cr.…”
Section: Introductionsupporting
confidence: 89%
“…Figure 2 displays the weight change versus time of the 12 and 17 μm fibers, compared with the 40 µm fibers’ TGA results obtained from Ibrahim et al [ 36 ]. The inset in Figure 2 shows the weight change versus time during the first complete MSHT cycle.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations